KESEJAHTERAAN KELUARGA PETANI KARET DI JORONG SITUGAR DAN JORONG PADANG LAWEH NAGARI TANJUANG BONAI - yanti, elfi da; Suasti, Yurni (JURNAL BUANA, 2024)
Jorong Situgar and Jorong Padang Laweh are located in Nagari Tanjuang Bonai, North Lintau Buo District, Tanah Datar Regency with rubber livelihoods. Rubber is the life support for the people in Jorong Situgar and Jorong Padang Laweh, the sale of rubber is income for rubber farmers. The income earned by the family of rubber farmers affects the fulfillment of the needs of clothing, food, and shelter. So by looking at the level of fulfillment of the needs of clothing, food, and housing for the family of rubber farmers, we can determine the welfare of the rubber farmers of Jorong Situgar and Jorong Padang Laweh. To observe the two Jorongs' well-being it can be seen by the amount of money that families engaged in the rubber farming industry spend on accommodation, food, and clothes. In order to compare the wellbeing of Jorong Situgar and Jorong Padang Laweh, a T-test was utilized as the research methodology. The findings of this study suggest that Jorong Padang Laweh's rubber farming family is more affluent than Jorong Situgar based on the amount of money spent on meeting necessities for clothing, food, and housing. Keywords: Jorong Situgar and Jorong Padang Laweh, meeting the needs of clothing, food and shelter, welfare.